1979
DOI: 10.1210/jcem-48-6-901
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin Insufficiency in Patients with Thalassemia Major*

Abstract: To elucidate whether the cause of sexual maturational arrest in thalassemia major is of hypothalamic or pituitary etiology, three female and two male patients were extensively studied. After the iv administration of 150 micrograms gonadotropin-releasing hormone (GnRH) and 500 micrograms of TRH, all patients demonstrated a minimal LH and no FSH response, with variable PRL and TSH responses. The test was repeated after the patients received 100 micrograms GnRH im daily for 7 days. The LH, FSH, PRL, and TSH respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
2

Year Published

1979
1979
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(44 citation statements)
references
References 0 publications
4
38
0
2
Order By: Relevance
“…Multiple gonadal and pituitary-gonadal function studies have confirmed primary gonadal failure due to gonadal iron deposition [27]. Secondary hypogonadism results from iron deposition on gonadotrophic cells of the pituitary gland as shown by poor response of FSH and LH to GnRH stimulation [28][29][30] or a combination of both primary and secondary hypogonadism [31].…”
Section: Hypogonadism and Puberty In Thalassaemiamentioning
confidence: 99%
“…Multiple gonadal and pituitary-gonadal function studies have confirmed primary gonadal failure due to gonadal iron deposition [27]. Secondary hypogonadism results from iron deposition on gonadotrophic cells of the pituitary gland as shown by poor response of FSH and LH to GnRH stimulation [28][29][30] or a combination of both primary and secondary hypogonadism [31].…”
Section: Hypogonadism and Puberty In Thalassaemiamentioning
confidence: 99%
“…Many endocrine deficiencies were attributed to the deposition of iron in endocrine glands of thalassaemic patients 6 . Endocrine abnormalities includes panhypopituitarism 7 , abnormal secretion of luteinizing hormone (LH) and follicle stimulating hormone (FSH) 8 , hypogonadism 9 , hypoparathyroidism 10 , elevated serum adrenocorticotropic hormone (ACTH) level with decreased adrenal cortical reserve 11 and diabetes mellitus 12 .…”
Section: Table 1: Demographic Profile Of Study Populationmentioning
confidence: 99%
“…All our patients had secondary hypogonadism with low basal FSH and LH indicating hypothalamic-pituitary damage. This is likely to be secondary to iron deposition on gonadotrophic cells of the pituitary gland (22)(23)(24). Among patients with thalassaemia major, an impact of the genotype on gonadal function also has been documented (25).…”
Section: Discussionmentioning
confidence: 99%